Tinjauan Hukum Ekonomi Syariah Terhadap Perjanjian Kerja Dalam Pembuatan Kapal Pinisi - Bahriansyah; Hamdan Mahmud; Muhammad Syarif Hidayatullah (STIS DAFA MATARAM, 2023)
The background of this research is that in the practice of making pinisi boats in Pagarruyung Village, Kusan Hilir District, Tanah Bumbu Regency, problems can occur, namely if the shipbuilding has been completed, but the buyer does not have the money to pay for it, then the ship is detained. The study aims to determine whether the impact if the agreement is not in accordance with the agreement at the beginning is felt by the builders and customers of the ship in Pagarruyung Village, Kusan Hilir District, Tanag Bumbu Regency. This research is a qualitative descriptive research with a case study approach. With this research subject, the parties involved or who know about the Pinisi shipbuilding work agreement by the customer and the shipbuilder. As for the data obtained from research, namely through observation, interviews, and documentation through the process of collecting data and analyzing the data. Based on the data that has been explained that in carrying out work on shipbuilding pinisi using an oral agreement, where the contents of the agreement discuss the shape, model, size, height, price, payment system, time period, etc. depending on the agreement of the two parties in the initial agreement. the impact if there is a discrepancy in the agreement at the beginning if the payment system is borne by the shipbuilder, for example the maker has completed the work on time, but the buyer does not have the money to pay for it, then the shipbuilder will suffer a loss. In the view of Islamic law, in the case that the work agreement for the manufacture of the Pinisi ship had not been justified by Islamic law, it contained harm related to the discussion, an error was found, namely: the customer violated the agreement at the beginning.